Conditional Sentences in Written Chinese - Lister, Anthony (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2002)
This paper examines real, hypothetical and counterfactual conditional sentences in written Chinese, and in particular focuses on two aspects: the forward and backward-linking elements, and the use of auxiliary verbs. The linking elements have received much attention in previous studies while the auxiliaries which occur in the main clause have attracted little interest. However the conditional sentences examined for this study show that these auxiliaries are very common and do play a special role in these types of constructions. It is possible that they could be considered as further markers of some types of conditional sentences, in much the same way that would or would have indicate conditional sentences in English.